ChemInform Abstract: Rhodium‐Catalyzed/Copper‐Mediated Tandem C(sp2)—H Alkynylation and Annulation: Synthesis of 11‐Acylated Imidazo[1, 2‐a:3, 4‐a′]dipyridin‐5‐ium‐4‐olates from 2H‐[1, 2′‐Bipyridin]‐2‐ones and Propargyl Alcohols. Issue 29 (June 2016) - Li, Ting; Wang, Zhiqiang; Xu, Kun; Liu, Wenmin; Zhang, Xu; Mao, Wutao; Guo, Yongming; Ge, Xiaolin; Pan, Fei
Abstract: The scalable title reaction tolerates variously functionalized 2H‐[1, 2′‐bipyridin]‐2‐ones as well as aryl and hetaryl substituted propargyl alcohols, but no alkyl substituted derivatives of the latter.